Folding induced supramolecular assembly into pH-responsive nanorods with a protein repellent shell. Issue 4 (18th December 2017) - Otter, R.; Klinker, K.; Spitzer, D.; Schinnerer, M.; Barz, M.; Besenius, P.
Abstract : ABA′ triblock peptide–polysarcosine–peptide conjugates fold into antiparallel β-sheets, which promotes the self-assembly into polysarcosine-shielded core–shell nanorods with protein repellent properties. Abstract : We report the synthesis of ABA′ triblock peptide–polysarcosine–peptide conjugates featuring two complementary phenylalanine–histidine pentapeptide strands A/A′. These sequences encode for antiparallel β-sheet formation into folded conjugates, which promote the self-assembly into polysarcosine-shielded core–shell nanorods. These do not cause aggregation of serum proteins in human blood plasma underlining an enhanced stability.